Data Science and Big Data Technologies Role in the Digital Economy - Sergey V. Novikov (TEM Journal, 2020)
This article explores the role of Data Science and Big Data technology in the modern digital economy. The author states that large and medium companies from retail trade and service sector show increased interest in using them. These technologies are actively used by banks, mobile operators and large manufacturing companies to analyze data on equipment failures and to reduce downtime, which allows reducing costs. The role of Big Data technology is to be a liquid product and a necessary condition to increase the profitability of enterprises through personalized customer service and predictive analytics. For today's Russian digital economy, it is very important to legalize a single definition of Big Data and to achieve the emergence of special data exchanges.